Case report: The success of empagliflozin therapy for glycogen storage disease type 1b - Klinc, Ana; Groselj, Urh; Mlinaric, Matej; Homan, Matjaz; Markelj, Gasper; Mezek Novak, Ajda; Sirca Campa, Andreja; Sikonja, Jaka; Battelino, Tadej; Zerjav Tansek, Mojca; Drole Torkar, Ana (Frontiers in Endocrinology, 2024)
Glycogen storage disease type 1b (GSD-1b) is characterized by neutropenia and neutrophil dysfunction generated by the accumulation of 1,5-anhydroglucitol-6-phosphate in neutrophils. Sodium-glucose co-transporter 2 inhibitors, such as empagliflozin, facilitate the removal of this toxic metabolite and ameliorate neutropenia-related symptoms, including severe infections and inflammatory bowel disease (IBD). Our case series presents the treatment of three paediatric GSD-1b patients with empagliflozin over a follow-up of three years; the most extended reported follow-up period to date.Cases Description. A retrospective analysis of empagliflozin treatment was performed for of three paediatric GSD-1b patients (two male and one female; ages at treatment initiation: 4.5, 2.5 and 6 years) was performedin Slovenia. Clinical and laboratory data from a symmetrical period of up to three years before and after the therapy introduction was reported. Data on the clinical course of the treatment, IBD activity, the need for antibiotic treatment and hospitalizations, neutrophil count and function, and markers of inflammation were assessed. Before Prior the introduction of empagliflozin, patients had recurrent oral mucosa lesions and infections, abdominal pain, and anemia. During empagliflozin treatment, the resolution of aphthous stomatitis, termination of abdominal pain, reduced frequency and severity of infections, anemia resolution, increased appetite, and improved wound healing was observed in all patients, as well as an increased body mass index in two of them. In a patient with IBD, long-term deep remission was confirmed. An increased and stabilized neutrophil count and an improved neutrophil function enabled the discontinuation of G-CSF treatment in all patients. A trend of decreasing inflammation markers was detected.During the three-year follow-up period, empagliflozin treatment significantly improved clinical symptoms and increased the neutrophil count and function, suggesting that targeted metabolic treatment could improve the immune function in GSD-1b patients.